2019
DOI: 10.14366/usg.18055
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of automated versus handheld breast ultrasound examinations of suspicious breast masses

Abstract: Purpose The purpose of this study was to assess the reliability of automated breast ultrasound (ABUS) examinations of suspicious breast masses in comparison to handheld breast ultrasound (HHUS) with regard to Breast Imaging Reporting and Data System (BI-RADS) category assessment, and to investigate the factors affecting discrepancies in categorization. Methods A total of 135 masses that were assessed as BI-RADS categories 4 and 5 on ABUS that underwent ultrasound (US)-g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
14
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 23 publications
1
14
0
Order By: Relevance
“…Yun et al, in a study performed on 135 asymptomatic women, noted that the agreement in confirmed malignancies was 55.1% (kappa = 0.39, P <0.001). 15 In our study group, the agreement on the BI-RADS category between ABUS and HHUS for confirmed malignant breast tumors was good (86.63%, kappa = 0.77). Among the discrepancies in all malignant cases, the BI-RADS assessment category assigned using ABUS tended to be higher than HHUS.…”
Section: Discussionmentioning
confidence: 51%
“…Yun et al, in a study performed on 135 asymptomatic women, noted that the agreement in confirmed malignancies was 55.1% (kappa = 0.39, P <0.001). 15 In our study group, the agreement on the BI-RADS category between ABUS and HHUS for confirmed malignant breast tumors was good (86.63%, kappa = 0.77). Among the discrepancies in all malignant cases, the BI-RADS assessment category assigned using ABUS tended to be higher than HHUS.…”
Section: Discussionmentioning
confidence: 51%
“…The k value is not only higher than those reported for real-time m-US but also higher than most κ values found for BI-RADS agreement in studies retrospectively reviewing static images (Table 5 ). Comparing final BI-RADS assessment in automated breast ultrasound (ABUS) and m-US agreement k values of 0.61[ 35 ] and 0.49 [ 37 ] in a selected study population, and k value of 0.99 [ 36 ] in a screening situation have been reported. In daily clinical practice, the management of patients with breast disease is largely determined by the final BI-RADS classification [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, lower diagnostic sensitivity and speci city restricted the use of ABUS [31]. Therefore, it is critical to determine independent breast NML risk factors to enhance diagnostic capability.…”
Section: Discussionmentioning
confidence: 99%